2022
DOI: 10.1161/circgen.121.003464
|View full text |Cite
|
Sign up to set email alerts
|

Familial Recurrence Patterns in Congenitally Corrected Transposition of the Great Arteries: An International Study

Abstract: Background: Congenitally corrected transposition of the great arteries (ccTGA) is a rare disease of unknown cause. We aimed to better understand familial recurrence patterns. Methods: An international, multicentre, retrospective cohort study was conducted in 29 tertiary hospitals in 6 countries between 1990 and 2018, entailing investigation of 1043 unrelated ccTGA probands. Results: Laterality defects and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Intriguingly, a recent WGS analysis showed that abnormalities in cilia-related genes were similar between TGA patients and controls [ 56 ]; in this context, the clustering of several variants in cilia genes could be relevant to identifying susceptibility genotypes that could increase the familiar risk related to cilia defects. Interestingly, a recent report described familial co-segregation of ccTGA and dextro-TGA [ 57 ]. ccTGA has been consistently associated with laterality defects [ 2 , 3 ], and these findings suggest a common pathogenic pathway involving laterality genes in both defects.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent WGS analysis showed that abnormalities in cilia-related genes were similar between TGA patients and controls [ 56 ]; in this context, the clustering of several variants in cilia genes could be relevant to identifying susceptibility genotypes that could increase the familiar risk related to cilia defects. Interestingly, a recent report described familial co-segregation of ccTGA and dextro-TGA [ 57 ]. ccTGA has been consistently associated with laterality defects [ 2 , 3 ], and these findings suggest a common pathogenic pathway involving laterality genes in both defects.…”
Section: Discussionmentioning
confidence: 99%
“…One large class of CHD are those related to laterality defects. Classically the laterality defect classification has included situs inversus totalis (complete mirror-image reversal of the chest and abdominal organs usual positions) and heterotaxy (a state of partial rearrangement or anatomical positioning with regard to the body axes) [ 4 ]. However, both animal and human published studies suggest that other CHD lesions could be due to altered laterality development of the heart [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classically the laterality defect classification has included situs inversus totalis (complete mirror-image reversal of the chest and abdominal organs usual positions) and heterotaxy (a state of partial rearrangement or anatomical positioning with regard to the body axes) [ 4 ]. However, both animal and human published studies suggest that other CHD lesions could be due to altered laterality development of the heart [ 4 7 ]. In fact, 3–7% of all apparently isolated CHDs, comprising double outlet right ventricle (DORV), atrioventricular canal defect (AVCD), or transposition of the great arteries (TGA), have been suggested to arise from abnormal embryonic L-R axis patterning [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is most often of sporadic appearance. However, there are some rare familial cases reported in the literature 7 8 . These reported pedigrees suggest a common pathogenetic pathway involving laterality genes in the pathophysiology of CCTGA.…”
Section: Introductionmentioning
confidence: 99%